(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the development of a comprehensive foreign trade strategy for Uzbekistan, focusing on improving the country’s economic potential by increasing exports, reducing imports, and attracting investment. Uzbekistan attaches great importance to the export of natural resources such as cotton, gas and gold. At the same time, in order to develop the economic potential of Uzbekistan, a lot of emphasis has been placed on other sectors, in particular, electricity, production, and industry. This serves to develop diversification. Explores the importance of strengthening international trade relations, primarily in Central Asia, as well as greater market access through global trade agreements and partnerships. The document contains the necessary reforms to remove obstacles and improve the competitiveness of Uzbekistan in international markets, infrastructure, development of human capital efficiency and acceleration of trade. At the same time, he emphasizes the possibilities of using innovative technologies and e-commerce platforms to develop economic integration and increase the volume of exports. Ultimately, the article suggests an effective approach to foreign trade strategy that combines policy reform, economic investment, and capacity building to position the country as a dynamic and sustainable player in the global economy.